FETTUCINI SCHOTEL DENGAN TAMBAHAN IKAN LELE SEBAGAI MAKANAN TINGGI PROTEIN UNTUK MILENIAL - Ardy, Lona Novian; Chayati, Ichda (Prosiding Pendidikan Teknik Boga Busana, 2021)
Fish are all kinds of organisms that span or in part of their life cycles in the water environment. However, the amount of fisheries potential in Indonesia is not consistent with the rate of fish consumption in Indonesia particularly in the second quarter. The lack of the variety of diet prepared from fish also contributes to a lack of interest in fish in the millennials. The study is aimed at increasing the consumption rate of fish within the millennials by adding catfish meat to the fettucini schotel, specifying recipes and finding public acceptance. The type of research used in this study is research and development with a model 4d (define, design, development and lubricated). This research analysis is a descriptive analysis. The respondents in this study comprise 30 untrained panelists who are in the vicinity of researchers. Based on the research the accepted and preferred formula for society is a product with a 30% increase in catfish from the total amount of wheat flour in pasta. It is based on the test t performed by researchers by viewing the average results of each product’s characteristics (color, taste, texture, scent, and overall). Keywords : Catfish, Food for millenial